Shunet el-Zebib Documentation and Conservation - O’Connor, David; Adams, Matthew D.
The funerary monument of King Khasekhemwy in Abydos is also known as the Shunet el-Zebib. Little is known about King Khasekhemwy, the last king of the Second Dynasty, but his reign ended in 2686 BC, making Shunet el-Zebib among the oldest surviving mud-brick structures in the world and the best example of Egypt’s earliest tradition of royal mortuary building. Funding from the Egyptian Antiquities Project (EAP) between 1999 and 2006 resulted in documentation and conservation of approximately 50% of the 200-meter perimeter using newly made mud bricks of the same size and originally sourced materials to re-establish structural integrity.